PERBEDAAN PERSEPSI ANTARA MAHASISWA SENIOR DAN JUNIOR MENGENAI PROFESI AKUNTAN PADA PROGRAM S-1 REGULER DAN STRANSFER PTS “X” - Elma Muncar Aditya (STIE Pelita Nusantara Semarang, 2010)
The purpose of this research is to observe whether there is different perception between senior students and junior students regarding accounting profession at Regular Program and Transfer Program. The hypothesis is tested using Mann Whitney test. The result of this research shows that at Regular Program, the senior students’ perception towards “accountant as a Profession and accounting as a Science” is lower than the junior students’ perception.At Transfer Program, the senior students’ perception towards “accountant as a Profession” is higher than the junior students’ perception. The research shows that the more senior they are (the longer they join the accounting education), the more they do not like accounting and do not want to have a career as an accountant.